Carbon dots: their types, obtaining methods, properties and applications - Auyelkhankyzy М.; Zhamash А.; Rakhymzhan Н.; Auyelkhankyzy М.; Lesbayev Б.Т. (Recent Contributions to Physics, 2025)
Nanotechnology is an interdisciplinary field at the intersection of fundamental and applied sciences and technology. This field makes it possible to obtain new and useful materials by manipulating materials that are not available in traditional ways at the atomic and molecular levels. One of the zero-dimensional nanomaterials that has been rapidly developing in this field in recent years due to the diverse properties it exhibits is carbon dots. Carbon dots are attractive carbon nanomaterials with properties suitable for use in photocatalysis, light-emitting devices, and sensors. This review article focuses on the history of carbon dots, starting from the first steps taken in the study of carbon dots, i.e., from the name of these nanomaterials "fluorescent nanoparticles" in 2004, to the development history, i.e., from 2011 to the present. It is proposed to consider carbon dots as graphene quantum dots, carbon quantum dots, and carbonized polymer dots, and they are compared and studied in detail. In addition, the “Top-down” and “bottom-up” approaches used in the synthesis of these carbon dots and their related methods were reviewed. Due to the increasing interest in carbon dots due to their diverse properties, their optical, electrochemical properties, dispersibility and toxicity were characterized. At the end of this article, the application of carbon dots in sensors, biomedicine, phototherapy, energy storage and catalysis are fully reviewed.